2023
DOI: 10.3390/cells12182253
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Oligonucleotides: An Outlook on Chemical Strategies to Improve Endosomal Trafficking

Priyanka Mangla,
Quentin Vicentini,
Annabelle Biscans

Abstract: The potential of oligonucleotide therapeutics is undeniable as more than 15 drugs have been approved to treat various diseases in the liver, central nervous system (CNS), and muscles. However, achieving effective delivery of oligonucleotide therapeutics to specific tissues still remains a major challenge, limiting their widespread use. Chemical modifications play a crucial role to overcome biological barriers to enable efficient oligonucleotide delivery to the tissues/cells of interest. They provide oligonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 280 publications
(384 reference statements)
0
2
0
Order By: Relevance
“…The rate of this cleavage after incubation with DNAse I was analyzed by PAGE (Figure 7B, S15–S17) and showed that C 6 is cleaved at a lower rate than all S 6 SNAs, crosslinked or not. After the action of endonucleases in the endolysosomal network, [39,40] several pathways of endosomal escape could occur for the FASO, as described in the literature [41,42] . The intracellular trafficking of phosphorothioated oligonucleotides has been widely studied and explains their higher activity as compared to non‐modified ASOs [43–45] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of this cleavage after incubation with DNAse I was analyzed by PAGE (Figure 7B, S15–S17) and showed that C 6 is cleaved at a lower rate than all S 6 SNAs, crosslinked or not. After the action of endonucleases in the endolysosomal network, [39,40] several pathways of endosomal escape could occur for the FASO, as described in the literature [41,42] . The intracellular trafficking of phosphorothioated oligonucleotides has been widely studied and explains their higher activity as compared to non‐modified ASOs [43–45] .…”
Section: Resultsmentioning
confidence: 99%
“…After the action of endonucleases in the endolysosomal network, [39,40] several pathways of endosomal escape could occur for the FASO, as described in the literature. [41,42] The intracellular trafficking of phosphorothioated oligonucleotides has been widely studied and explains their higher activity as compared to non-modified ASOs. [43][44][45] From these experiments, S 6 and S 6x SNAs show the most promise for unaided gene silencing, as they are able to dissociate intracellularly due to their bioreducible core and release the FASO therapeutic the most efficiently.…”
Section: Methodsmentioning
confidence: 99%